Exploring the within-person contemporaneous network of motivational engagement. (October 2022) - Tamura, Ayame; Ishii, Ryo; Yagi, Ayano; Fukuzumi, Noriaki; Hatano, Aya; Sakaki, Michiko; Tanaka, Ayumi; Murayama, Kou
Abstract: Existing theoretical frameworks on motivation have identified a number of critical components in our motivational engagement process in learning. However, little empirical research has examined how these different components interact with each other to support our overall motivational engagement. This study explores such dynamics in a bottom-up manner by examining the within-person contemporaneous network structure of key components in the motivational engagement process (i.e., reasons/values, expectancy belief, goals, social relations, affective experiences, and perceived autonomy). We tracked four participants working on psychological research projects over the course of a year on a daily basis, and found that their motivational engagement mainly consisted of a large network of nodes that support autonomous forms of self-regulation. Scrutiny of the network also suggests the critical roles of curiosity and intrinsic reason in bridging affective and core motivational aspects of engagement. Highlights: A number of critical components in motivational engagement have been identified. However, it is still unclear how these components interact with each other. We tracked four participants over a year to explore the within-person network. There is a large network of nodes that support autonomous forms of self-regulation. Findings contribute understanding people's motivational engagement process.